2014
DOI: 10.1007/s00431-014-2401-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and sequelae for tick-borne encephalitis among children in South Moravia (Czech Republic)

Abstract: Tick-borne encephalitis in children has a benign course with minimal sequelae. Meningitis with biphasic course is the prevalent involvement and the duration of IgM antibodies in serum and index of positivity are not decisive for postencephalitic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 47 publications
2
26
0
2
Order By: Relevance
“…In total, 37 clinical studies published between 1975 and 2020 were included [ 3 , 4 , 6 , 7 , 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] ( Table 6 ). The distribution of diagnoses showed the frequency of M ranging from 7 to 78%, ME from 13 to 84%, and MEM from 3 to 11%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 37 clinical studies published between 1975 and 2020 were included [ 3 , 4 , 6 , 7 , 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] ( Table 6 ). The distribution of diagnoses showed the frequency of M ranging from 7 to 78%, ME from 13 to 84%, and MEM from 3 to 11%.…”
Section: Resultsmentioning
confidence: 99%
“…Although we observed severe cases, none of the pediatric cases died. A relatively low mortality rate in children and adolescents has been reported before [ 31 , 44 , 45 ]. According to our findings and to the findings of the literature review, no significant decrease in mortality rates during the last decades was found.…”
Section: Discussionmentioning
confidence: 96%
“…In children, TBE infection is described as having a mild clinical course. TBE under the age of three years is rare, and the mean age of the meningoencephalitic form of TBE is 14 years [ 10 ]. The reason why childhood TBE is usually less severe than TBE in adults is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Encephalitis can also be caused by autoimmune disorders, but these are beyond the scope of the current review. Infectious encephalitis typically triggers fever, seizures, and focal neurologic deficits (Khatib et al, 2017;Krbková et al, 2015;Sittinger et al, 2002). Diagnosis is similar to that of meningitis, in that it may include a lumbar puncture, neurological and radiological examinations (Tyler & Ropper, 2018).…”
Section: Introductionmentioning
confidence: 99%